Child Free Perspektif Agama Hindu - Hari Harsananda; Mery Ambarnuari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
After the second world war, the increase in the world's population was so rapid that it raised issues of environmental damage, food security, and increased crime cases. This causes some densely populated countries to limit the number of births. The birth of a child leaves a carbon footprint of up to 58.6 tons/year. This is what causes the Childfree movement to emerge as one of the solutions offered by modern humans in overcoming environmental issues. The driving factors include environmental awareness, to a consumptive lifestyle due to capitalist ideology. Hinduism in its teachings views that having children is a obligation for parents because children can be the glue of husband-wife relationships and having children who are suputra is the main Yajna. Intelligent children will be able to solve the problems they face, including environmental issues which became the initial basis for the Child free movement. So not having children is not the only solution to overcome environmental damage. The method used in this article uses a qualitative method and uses a phenomenological approach which is described descriptively. The data in this article was obtained through literature studies, both from articles published in journals, Hindu religious sacred texts combined with analysis of data obtained and sourced from the internet in the form of documents, news to videos that are shown on the YouTube platform.